PROPOSE THE BEST SMART DEVICE FOR PT.PLN (PERSERO) UP2D WEST JAVA USING ANAYLITICAL HIERARCHY PROCESS DUE TO SUPPORTING PREVENTIVE OF MASSIVE OUTAGE AT 20 KV SUBSTATION IN WEST JAVA REGION (The Indonesian Journal of Business Administration, 2021)
West Java region is the region with the largest number of revenue suppliers for PLN because many customers in the region are from the industrial sector. Based on existing data from 2017 to 2020, the massive outage that occurred in the West Java region was still relatively high. According to its condition, Focus Group discussion was conducted to determine the main cause. Problem solving from the results is to implement smart device which functions to measure the variable causes of the problem in real time to prevent circuit breaker trips at the substation which causes widespread power outages on the customer side. In selecting smart devices, this research uses Analytic Hierarchy Process tools. There are 4 choices of smart devices in this research, namely innovation products, IntellSAW, TH110, and SPS. These smart devices are compared with several criteria which include features, value proposition, ease of use, product price, maintenance cost, installation cost, lifetime approximately, product guarantee and brand value. Furthermore, the process of selecting smart devices is carried out through a questionnaire given to 3 divisions, namely top management, operational division and non-operational division. The smart device chosen by respondents using the Analytic Hierarchy Process method is IntellSAW with the highest percentage of the overall score of 45.88%. Likewise, with the calculation of scores in each division, IntellSAW has the highest percentage score in the top management division at 45.11%, in the operational division with a score percentage of 54.82%, and in non-operational divisions with a score percentage of 36.15%. With the results of this election, IntellSAW will be applied to certain substations in the West Java region. Keyword: Analytical Hierarchy Process, smart devices, outages, focus group discussion, IntellSAW